Resources Exchange Model in Implementation Network of Fishermen Community Policy in Makassar City - SUSANTI, GITA; ALWI, ALWI; TAMBA, LA (Universitas Muhammadiyah Yogyakarta, 2017)
Public policy implementation network is a study that tried to accumulate all the stakeholders as potential resources to determine and implement a public policy. Fishermen community empowerment policy is the policy, which is complex be- cause it includes varied stakeholders. The main objective of this study is to develop a model of resources exchange in the implementation network of fisher- men community empowerment policy in Makassar City, which includes the avail- ability of resources and the rule of the game of resources exchange. This study uses qualitative design and case study strategy. Based on the pairing patterns technique, the availability of the resources needed by the fishermen group has not been sufficient to run his business. This is caused by a major source of fund- ing in this policy from the central government. Then, the fishermen community empowerment policy is still dominated by rule of the game of public bureau- cracy as the policy implementer in the resources exchange. Therefore, local gov- ernments need to develop the synergy with all stakeholders and establish a rule of the game based on the network-based organization.